Factors Associated with Perception and Knowledge of Punjab’s Farm Youth about Stubble Management - Ekta,; Sharma, Preeti; Kaur Mann, Sukhdeep; Singh Kishnawat, Lokendra (Indian Journal of Extension Education, 2025)
The study, conducted in 2025, examined how socio-personal variables were associated with the perception and knowledge of farm youth toward stubble management, and how family and farming-related characteristics were associated with families’ involvement in stubble burning. A structured questionnaire was administered to 720 respondents selected through multistage purposive and random sampling from five agro-climatic zones of Punjab. Data were analysed using chi-square and Fisher’s exact tests to determine associations between variables. Gender and caste showed significant associations with both perception and knowledge. School type and medium of education showed no significant association with either variable. Family type was significantly associated with knowledge but not with perception. Among family and farming variables, caste and landholding size were significantly associated with the family’s involvement in stubble burning, while family size, family educational status, and number of earning members showed no significant relationship. Overall, the results indicated that a combination of socio-personal characteristics and structural agricultural factors shaped stubble management behaviour. The study concluded that enhancing perception and knowledge among rural youth, particularly youth enrolled in Punjabi-medium and government schools, and those belonging to the general caste and large landholding families are essential for fostering long-term behavioural change.